E-commerce and territorial development in the Objective-1 spanish regions - Juan Carlos Rodriguez Cohard; Enrique Bernal Jurado (European Regional Science Association (ERSA), 2002)
The information and communication technologies constitute one of the main forces of the globalization. In this framework, the e-commerce takes advantage of Internet to improve the competitiveness of the companies and territories. In the nowadays scenario, the e-commerce opens development posibilities for the regions fewer developed, creating a virtual space that saves the geographical barriers. However, the use of its advantages requires infrastructures and equipment, organizational capacity and high formation in new technologies. In spite of the deficit that the objetive 1 spanish regions show in these fields to develop the their own Information Society, the attitude and the efforts of the public and private agents in improving their position in the national and international context, they open optimistic expectations on the future use of the advantages that the e-commerce offers for the growth and the improvement of the regional competitiveness in Spain. Nevertheless, one cannot hope the e-commerce is a decisive element to eliminate the territorial inequalities, not even the technologies of the information in its group, but rather it can be that they originate a restructuring of the spanish and european territorial pattern, where some regions will be able to improve thanks to the extension and deeping of the digital economy and others will worsen its position in the territorial system. In any event, the developed regions leave of a better position. All the analysts coincide in pointing out that the e-commerce is in an incipient phase, for what es expected that its growth in next years is very important. In this sense, this communication seeks to analyze the use of the possibilities that the e-commerce offers as tool of improvement of the competitiveness in the objetive 1 spanish regions in the framework of the regional development. To get this objetive, the theoretical linkings are revised among the new information and communication technologies, that allow the use of Internet like a trade channel, and the territorial development, showing the different focuses with those that are come approaching the influences of the Information Society on the regional competitiveness. Also, the current situation and perspectives of the objetive one spanish regions are rewied to face the challenges that outline the technological advances in this field in three environments: infrastructures and equipment; organization, support institutions and administration initiatives; and innovation, knowledge and formation.
Keywords: 330